Method for preparing micron-sized neodymium-doped yttrium aluminum garnet single crystal film on SiO2 / Si substrate
By using thermal oxidation, direct bonding, wafer grinding and chemical mechanical polishing on SiO2/Si substrates, it is difficult to prepare micron-scale neodymium doped yttrium aluminum pomegranate with good single crystallinity and uniform thickness in the prior art. The problem of stone single crystal thin film has achieved high-quality film preparation.
Patent Information
- Application Number
- CN202411466713.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-11
AI Technical Summary
It is difficult to prepare micron-order neodymium doped yttrium aluminum garnet (Nd:YAG) single crystal thin films with good single crystallinity and uniform thickness on SiO2 substrates.
Thermal oxidation method is used to form a silicon dioxide film on the silicon substrate wafer. The neodymium-doped yttrium aluminum garnet wafer is contact bonded with the silicon dioxide film through direct bonding. After annealing, the neodymium-doped yttrium aluminum garnet wafer is used to contact and bond. Yttrium aluminum garnet wafers are ground to the film and polished to the target thickness by chemical mechanical.
The thickness uniformity of the neodymium-doped yttrium aluminum garnet single crystal film is significantly improved, ensuring good single crystalline properties and surface flatness of the film, and realizing the preparation of micron-level neodymium-doped yttrium aluminum garnet single crystal on SiO2/Si substrate The goal of film.
Smart Images

Figure CN119411229A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical material films, and in particular to a method for preparing a micron-level Nd:Yttrium aluminum garnet single crystal film on a SiO2 / Si substrate. Background Art
[0002] Neodymium-doped yttrium aluminum garnet (Nd:YAG) crystal has excellent optical and physical properties and is one of the most important and widely used solid laser gain materials. 3+ ), the YAG lattice will not be distorted, so it maintains excellent performance. Nd:YAG crystal has excellent optical and thermomechanical properties (high emission cross section, large pump absorption coefficient, high diffusion coefficient and low expansion coefficient), and is one of the solid laser materials with the best comprehensive properties. Nd:YAG crystal can produce lasers with wavelengths of 1318nm, 1064nm and 946nm, especially at a wavelength of 1064nm, with a quantum efficiency of up to 99.7%. At the same time, Nd:YAG has good stability, and its fluorescence lifetime, quantum efficiency and line width are basically unaffected by temperature changes at room temperature. This allows it to exhibit stable and reliable performance in many application fields.
[0003] The greater the refractive index difference between the thin film waveguide and the surrounding environment, the stronger the restriction on light. Therefore, the preparation of a thin film waveguide structure with a high refractive index difference with the surrounding medium is the key to realizing a highly integrated Nd:YAG on-chip integrated laser. At the same time, the clearer the interface of the thin film material and the higher the degree of single crystal, the more it can avoid light scattering on the interface and reduce light transmission loss. Therefore, the interface clarity and single crystal degree of the film become important indicators of film quality. Although researchers have tried a variety of technologies for preparing YAG single crystal films (pulsed laser deposition, sol-gel, ion implantation, etc.), the single crystal degree of the films prepared by these methods has certain defects, and it is not possible to prepare micron-thick Nd:YAG single crystal films on low refractive index substrates such as SiO2.
[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a method for preparing micron-sized Nd:Yttrium aluminum garnet single crystal thin film on a SiO2 / Si substrate, aiming to solve the problem of how to prepare micron-sized Nd:Yttrium aluminum garnet thin film with good single crystality and uniform thickness on a SiO2 substrate.
[0006] The technical solution of the present invention is as follows:
[0007] The present invention provides a method for preparing a micron-sized Nd:YAG single crystal thin film on a SiO2 / Si substrate, comprising the steps of:
[0008] S1, forming a silicon dioxide film on the upper surface of a silicon base wafer by a thermal oxidation method, and grinding the lower surface of the silicon base wafer by a grinding and polishing process to obtain a SiO2 / Si substrate;
[0009] S2, taking a (111)-oriented Nd:YAG wafer, contact-bonding the Nd:YAG wafer with the silicon dioxide film by direct bonding to obtain a bonded body, and performing annealing to obtain an annealed bonded body;
[0010] S3, grinding the Nd:YAG wafer in the annealed bonded body into a Nd:YAG film using a wafer grinding process, so that the surface of the Nd:YAG film is parallel to the surface of the silicon base in the SiO2 / Si substrate;
[0011] S4. The Nd:YAG film is chemically mechanically polished to a target thickness to obtain a micron-sized Nd:YAG single crystal film formed on a SiO2 / Si substrate.
[0012] In step S1, optionally, the thickness of the silicon dioxide film is 2-4 μm.
[0013] In step S1, optionally, the step of grinding the lower surface of the silicon base wafer by a grinding and polishing process includes: using a high-precision single-sided grinder to grind the lower surface of the silicon base wafer, and after chemical mechanical polishing and cleaning, the total thickness of the silicon base in the SiO2 / Si substrate changes by less than 1μm.
[0014] In step S2, optionally, the initial thickness of the Nd:YAG wafer is 0.2-2 mm.
[0015] In step S2, optionally, the temperature of the annealing treatment is 150-200°C, and the time of the annealing treatment is 2-8 hours.
[0016] In step S3, optionally, the thickness of the Nd:YAG film is 5-10 μm.
[0017] In step S4, optionally, the chemical mechanical polishing uses a silicon dioxide polishing solution.
[0018] In step S4, optionally, the chemical mechanical polishing includes rinsing, brushing or ultrasonic cleaning the surface of the polishing pad during or after polishing.
[0019] In step S4, optionally, the thickness of the micron-scale Nd:YAG single crystal thin film formed on the SiO2 / Si substrate is 1-3 μm.
[0020] In step S4, optionally, the surface roughness of the micron-scale Nd:YAG single crystal thin film formed on the SiO2 / Si substrate is less than 0.5 nm.
[0021] Beneficial effects:
[0022] The invention provides a method for preparing a micron-sized Nd:YAG single crystal film on a SiO2 / Si substrate, wherein the total thickness variation of the SiO2 / Si substrate is optimized, and after being directly bonded to a Nd:YAG wafer, the Nd:YAG wafer is subjected to high-precision grinding to ensure that the surface of the Nd:YAG film and the surface of the silicon base in the SiO2 / Si substrate remain relatively parallel, thereby significantly improving the uniform thickness of the Nd:YAG single crystal film. Then, chemical mechanical polishing is performed to remove the surface damage caused by grinding, and finally a micron-sized Nd:YAG single crystal film with uniform thickness and good single crystallinity is prepared on the SiO2 / Si substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the preparation process of a micron-sized neodymium-doped yttrium aluminum garnet (Nd:YAG) single crystal thin film on a SiO2 / Si substrate in an embodiment of the present invention.
[0024] Figure 2 This is a macroscopic photograph of a micron-sized Nd:YAG single crystal thin film sample prepared in an embodiment of the present invention.
[0025] Figure 3 This is a focused ion beam electron microscope test image of the micron-sized Nd:YAG single crystal film prepared in an embodiment of the present invention.
[0026] Figure 4 This is a regional division diagram of the micron-sized Nd:YAG single crystal thin film prepared in an embodiment of the present invention.
[0027] Figure 5 This is a waveguide parameter result diagram of each area divided by the micron-scale Nd:YAG single crystal thin film prepared in an embodiment of the present invention. DETAILED DESCRIPTION
[0028] The present invention provides a method for preparing a micron-sized Nd:YAG single crystal thin film on a SiO2 / Si substrate. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0029] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0030] The embodiment of the present invention provides a method for preparing a micron-sized Nd:YAG single crystal thin film on a SiO2 / Si substrate, comprising the steps of:
[0031] S1, forming a silicon dioxide film on the upper surface of a silicon base wafer by a thermal oxidation method, and grinding the lower surface of the silicon base wafer by a grinding and polishing process to obtain a SiO2 / Si substrate;
[0032] In step S1, in some embodiments, the thickness of the silicon dioxide film is 2 μm.
[0033] Because the formation of Nd-doped YAG single crystal thin film waveguide requires the substrate refractive index to be lower than the refractive index of the Nd-doped YAG single crystal thin film, the refractive index of silicon dioxide is 1.45, which is lower than the refractive index of the Nd-doped YAG crystal (about 1.8), and the performance of silicon dioxide itself is stable, with low absorption rate in the visible light-near infrared band. At the same time, it can be obtained directly by oxidation on a silicon substrate, which is an ideal substrate material for preparing single crystal thin films.
[0034] In some embodiments, the step of grinding the lower surface of the silicon base wafer using a grinding and polishing process includes: using a high-precision single-sided grinder to grind the lower surface of the silicon base wafer, and after chemical mechanical polishing and cleaning, the total thickness of the silicon base in the SiO2 / Si substrate changes by less than 1 μm.
[0035] In the specific grinding process, a special parallel clamp is used to fix the film to ensure that the parallelism of the film will not be affected by the deformation or instability of the clamp during the grinding process. At the same time, the workpiece should be rotated or moved at a uniform speed to avoid uneven grinding caused by fixing a certain direction. The pressure applied to the workpiece should be kept uniform during the grinding process to avoid excessive local grinding. And ensure the flatness of the grinding disc itself. If the grinding disc is uneven, it will directly affect the parallelism of the film. After grinding, clean and dry, and then polish.
[0036] Generally speaking, the total thickness variation (TTV) of a silicon substrate wafer is usually in the range of 3-5 μm. The present invention performs high-precision grinding on the silicon substrate wafer and utilizes this grinding process to optimize the TTV of the silicon substrate to less than 1 μm.
[0037] S2, taking a (111)-oriented Nd:YAG wafer, contact-bonding the Nd:YAG wafer with the silicon dioxide film by direct bonding to obtain a bonded body, and performing annealing to obtain an annealed bonded body;
[0038] In step S2, in some embodiments, the initial thickness of the Nd:YAG wafer is 0.2-2 mm.
[0039] In some embodiments, the annealing temperature is 150-200° C., and the annealing time is 2-8 hours.
[0040] Through direct bonding technology, Nd:YAG wafers can be tightly bonded to silicon dioxide substrates. Direct bonding can reduce wafer damage and does not require the use of adhesives or other intermediate layers or external electric field assistance, thus avoiding contamination problems and interface defects that may be introduced by auxiliary materials. Compared with metal bonding, it avoids the problem that light in the Nd:YAG single crystal film will be absorbed by the metal bonding layer.
[0041] S3. Grind the Nd:YAG wafer in the annealed bonded body into a Nd:YAG film using a wafer grinding process, so that the surface of the Nd:YAG film remains parallel to the surface of the silicon base in the SiO2 / Si substrate.
[0042] In step S3, in some embodiments, the thickness of the Nd:YAG film after the wafer grinding process is 5-10 μm.
[0043] The embodiment of the present invention performs high-precision grinding on the Nd-doped YAG wafer in the bonded body after annealing, uses the same equipment and fixtures as when grinding the silicon substrate, and ensures that the surfaces of the Nd-doped YAG wafer and the silicon substrate remain relatively parallel, which can significantly improve the thickness uniformity of the micron-level Nd-doped YAG single crystal film located on the upper layer. When the Nd-doped YAG single crystal film is used to prepare integrated optical devices, its thickness uniformity will improve the device performance.
[0044] S4. The Nd:YAG film is chemically mechanically polished to a target thickness to obtain a micron-sized Nd:YAG single crystal film formed on a SiO2 / Si substrate.
[0045] In step S4, in some embodiments, the chemical mechanical polishing uses a silicon dioxide polishing solution. In a specific embodiment, the film thickness needs to be measured multiple times during the polishing process.
[0046] In some embodiments, the chemical mechanical polishing includes rinsing, brushing or ultrasonic cleaning the surface of the polishing pad during or after polishing.
[0047] In some embodiments, the micron-sized Nd:YAG single crystal thin film formed on the SiO2 / Si substrate has a thickness of 1 to 3 μm.
[0048] In some embodiments, the surface roughness of the micron-sized Nd:YAG single crystal thin film formed on the SiO2 / Si substrate is less than 0.5 nm.
[0049] The following describes it in detail through specific embodiments.
[0050] Example 1
[0051] The preparation process of micron-sized Nd:YAG single crystal thin films on SiO2 / Si substrate is as follows: Figure 1 As shown, the specific steps are as follows:
[0052] A 3-inch (111) oriented Nd:YAG wafer is used as an initial wafer for the Nd:YAG thin film, and the thickness of the initial Nd:YAG wafer is 0.3 mm.
[0053] A 3-inch silicon substrate wafer was used as the substrate wafer. A layer of silicon dioxide film was oxidized on the surface of the 3-inch silicon substrate by thermal oxidation to prepare a SiO2 / Si substrate material, wherein the thickness of the silicon dioxide film was about 2μm. A high-precision single-sided grinder was used to grind the back of the silicon substrate wafer. Through this grinding process, the total thickness variation (TTV) of the silicon substrate in the SiO2 / Si substrate was optimized to less than 1μm.
[0054] The silicon dioxide film in the SiO2 / Si substrate and the Nd:YAG wafer were directly bonded together at room temperature and then annealed at 200°C for 4 hours.
[0055] The initial Nd:YAG wafer in the bonded body after annealing was ground using a high-precision single-sided grinder to ensure that the surface of the Nd:YAG film and the surface of the silicon substrate remained relatively parallel. After the initial Nd:YAG wafer was ground to a thickness of about 5μm, the Nd:YAG film was polished to a thickness of about 3μm using a silicon dioxide polishing solution by chemical mechanical polishing (CMP) to remove surface damage caused by grinding and reduce the surface roughness of the film to less than 0.5nm. Finally, a micron-sized Nd:YAG single crystal film was obtained on a SiO2 / Si substrate.
[0056] The hybrid film wafer was cut into squares for subsequent performance characterization.
[0057] The macroscopic photograph of the micron-sized Nd:YAG single crystal thin film sample prepared in this embodiment is shown in FIG. Figure 2As shown, the area surrounded by the white dotted line is selected to study the waveguide characteristics of the Nd:YAG single crystal film. The area of the white area is about 3mm×3mm.
[0058] The micron-sized Nd:YAG single crystal thin film prepared on SiO2 / Si substrate was observed by focused ion beam electron microscopy (FIB). Figure 3 As shown, the obtained sample is Nd:YAG single crystal film, SiO2 film and Si substrate from top to bottom, wherein the thickness of Nd:YAG single crystal film is about 3 μm, and the thickness of silicon dioxide film is about 2 μm.
[0059] Waveguide properties test of Nd:YAG single crystal thin film
[0060] Since the thickness of the Nd:YAG single crystal film measured by focused ion beam electron microscopy is not accurate, in order to more accurately and reliably measure the refractive index and thickness of the Nd:YAG single crystal film, the prism coupling method is used for measurement. The prism coupling method can analyze different waveguide modes, accurately measure the refractive index and thickness of the film, and achieve non-destructive measurement. In order to analyze the thickness uniformity of the Nd:YAG single crystal film prepared in the experiment, Figure 2 The larger Nd:YAG single crystal film area enclosed by the white dotted line is divided into nine small areas. The regional division image of the Nd:YAG single crystal film is shown in the figure. Figure 4 shown.
[0061] The test conditions are: the working wavelength of the laser beam used is 1545nm, TE(s) polarized light is incident on the prism, and the code of the prism used is 4387.8 x For TE (s) polarized light, the prism refractive index is 2.6942; for TM (p) polarized light, the prism refractive index is 2.4439, both of which are greater than the refractive index of the Nd:YAG single crystal film used.
[0062] The effective refractive index of the waveguide in each region of the Nd:YAG single crystal film measured at 1545nm using a prism coupler is shown in Table 1. According to the effective refractive index of each mode, the iWKB method can be used to fit the refractive index distribution of the optical waveguide, thereby calculating the refractive index and thickness of each region of the Nd:YAG single crystal film.
[0063] Table 1 Waveguide effective refractive index of each region of Nd:YAG single crystal film
[0064]
[0065]
[0066] The dark mode curves of each region of the Nd:YAG single crystal film were measured at 1545nm using the above prism coupler. According to the effective refractive index of each mode, the iWKB method can be used to calculate the refractive index and thickness of each region of the YAG single crystal film. The waveguide parameters of each region of the Nd:YAG single crystal film are as follows: Figure 5 The refractive index and thickness of each region of the Nd:YAG single crystal film and their average values are shown in Table 2.
[0067] Table 2 Refractive index and thickness of each region of Nd:YAG single crystal film and their average values
[0068]
[0069]
[0070] It can be seen that the average refractive index of the micron-sized Nd:YAG single crystal film on the SiO2 / Si substrate prepared in the embodiment of the present invention is 1.8057, and the average thickness is 2.80μm. Compared with the Nd:YAG bulk material, the refractive index of the micron-sized Nd:YAG single crystal film is almost the same as that of the bulk material, and the maximum thickness deviation of the micron-sized Nd:YAG single crystal film in different regions is only 0.18μm, which has good thickness uniformity.
[0071] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a micron-sized Nd:YAG single crystal thin film on a SiO2 / Si substrate, characterized in that: Includes steps: S1, forming a silicon dioxide film on the upper surface of a silicon base wafer by a thermal oxidation method, and grinding the lower surface of the silicon base wafer by a grinding and polishing process to obtain a SiO2 / Si substrate; S2, taking a (111)-oriented Nd:YAG wafer, contact-bonding the Nd:YAG wafer with the silicon dioxide film by direct bonding to obtain a bonded body, and performing annealing to obtain an annealed bonded body; S3, grinding the Nd:YAG wafer in the annealed bonded body into a Nd:YAG film using a wafer grinding process, so that the surface of the Nd:YAG film is parallel to the surface of the silicon base in the SiO2 / Si substrate; S4. The Nd:YAG film is chemically mechanically polished to a target thickness to obtain a micron-sized Nd:YAG single crystal film formed on a SiO2 / Si substrate.
2. The method for preparing a micron-sized Nd:YAG single crystal thin film on a SiO2 / Si substrate according to claim 1, characterized in that: In step S1, the thickness of the silicon dioxide film is 2-4 μm.
3. The method for preparing a micron-sized Nd:YAG single crystal thin film on a SiO2 / Si substrate according to claim 1, characterized in that: In step S1, the step of grinding the lower surface of the silicon base wafer by a grinding and polishing process includes: using a high-precision single-sided grinder to grind the lower surface of the silicon base wafer, and after chemical mechanical polishing and cleaning, the total thickness of the silicon base in the SiO2 / Si substrate changes by less than 1μm.
4. The method for preparing a micron-sized Nd:YAG single crystal thin film on a SiO2 / Si substrate according to claim 1, characterized in that: In step S2, the initial thickness of the Nd:YAG wafer is 0.2-2 mm.
5. The method for preparing a micron-sized Nd:YAG single crystal thin film on a SiO2 / Si substrate according to claim 1, characterized in that: In step S2, the temperature of the annealing treatment is 150-200°C, and the time of the annealing treatment is 2-8 hours.
6. The method for preparing a micron-sized Nd:YAG single crystal thin film on a SiO2 / Si substrate according to claim 1, characterized in that: In step S3, the thickness of the Nd:YAG film is 5 μm.
7. The method for preparing a micron-sized Nd:YAG single crystal thin film on a SiO2 / Si substrate according to claim 1, characterized in that: In step S4, the chemical mechanical polishing uses a silicon dioxide polishing solution.
8. The method for preparing a micron-sized Nd:YAG single crystal thin film on a SiO2 / Si substrate according to claim 1, characterized in that: In step S4, the chemical mechanical polishing includes rinsing, brushing or ultrasonic cleaning the surface of the polishing pad during or after polishing.
9. The method for preparing a micron-sized Nd:YAG single crystal thin film on a SiO2 / Si substrate according to claim 1, characterized in that: In step S4, the thickness of the micron-sized Nd:YAG single crystal thin film formed on the SiO2 / Si substrate is 1-3 μm.
10. The method for preparing a micron-sized Nd:YAG single crystal thin film on a SiO2 / Si substrate according to claim 9, characterized in that: The surface roughness of the micron-scale Nd:YAG single crystal film formed on the SiO2 / Si substrate is less than 0.5 nm.